1999
DOI: 10.1046/j.1440-1622.1999.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure During Fluoroscopy: Should We Be Protecting Our Thyroids?

Abstract: Although RE without thyroid shields did not exceed current standards set by radiation safety authorities, no threshold level has been set below which thyroid carcinogenesis is unlikely to occur. Because lead shields are easy to wear and can effectively reduce RE to the thyroid region to near-background levels, they should be made easily available and used by all surgeons to avoid the harmful effects of radiation on the thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 7 publications
0
17
1
2
Order By: Relevance
“…The three different measurements of the dosimeters were all within the permissible range. Other studies have shown the radiation measurements for fluoroscopy-guided intervention pain procedures to be within the permissible range [6][7][8][9][10][11][12], but the natural radiation exposure dose in daily life is 2.4 mSv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three different measurements of the dosimeters were all within the permissible range. Other studies have shown the radiation measurements for fluoroscopy-guided intervention pain procedures to be within the permissible range [6][7][8][9][10][11][12], but the natural radiation exposure dose in daily life is 2.4 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical procedure in the operating room, according to shortness or length taken radiation doses, is different. Injuries to skin, muscle, and eye lens * corresponding author; e-mail: umitkara@sdu.edu.tr due to the radiation from fluoroscopic procedures have been widely documented [8][9][10]. In this study, we measured fluoroscopy unit in our university department of anaesthesia clinics to evaluate the mean fluoroscopy time and total radiation exposure for various treatment management procedures.…”
Section: Introductionmentioning
confidence: 99%
“…İyonize radyasyonun, tıpta kullanımı 1898'de Roentgen tarafından başlatılmıştır. X ışınları özellikle hekimler, hemşireler ve röntgen teknisyenleri için önemlidir 10 . Doğal radyoaktif maddeler olan radyum, uranyum ve toryum'un ve suni radyoaktif maddeler yani radyoaktif izotopların tıpta kullanımı sağlık çalışanları için risk oluşturmaktadır.…”
Section: Materyal Ve Metodunclassified
“…Avustralyalı ortopedistlerde tiroid kanserlerindeki artışı gösteren çalışmalar, ameliyathanelerde radyasyon güvenliğinin ne denli önemli olduğunu vurgulamıştır. Alınan doz düşük olsa bile süreklilik söz konusu olduğunda, vücutta birikim nedeni ile zararlı etkisini göstermekte özellikle gebelik döneminde olanlar için daha büyük tehlike oluşturmaktadır 10 International Comission on Radiological Protection (ICRP) tarafından bildirilen tüm vücut için kabul edilebilir maksimum doz yıllık 5000 mrem 'dir. Türkiye Atom Enerjisi Kurumu Nükleer Araştırma Merkezi de ''Radyasyon Güvenliği'' bildirisinde yıllık dozun 5000 mrem, ardışık beş yılın ortalamasının ise 2000 mrem olması gerektiğini belirtmiştir.…”
Section: Materyal Ve Metodunclassified
“…When distance from the source of radiation is doubled, the exposure to the practitioner is decreased by one-fourth. Shielding/protection of tissue include the use of lead aprons, thyroid shields [26,27], thick lead-lined gloves, leaded glasses, and lead shields. Use of dosimetry devices worn at the collar and finger are available and recommended to monitor exposure.…”
mentioning
confidence: 99%